Mitotic checkpoint regulator RAE1 promotes tumor growth in colorectal cancer. Issue 8 (14th June 2021) - Kobayashi, Yuta; Masuda, Takaaki; Fujii, Atsushi; Shimizu, Dai; Sato, Kuniaki; Kitagawa, Akihiro; Tobo, Taro; Ozato, Yuki; Saito, Hideyuki; Kuramitsu, Shotaro; Noda, Miwa; Otsu, Hajime; et al.
Abstract: Microtubules are among the most successful targets for anticancer therapy because they play important roles in cell proliferation as they constitute the mitotic spindle, which is critical for chromosome segregation during mitosis. Hence, identifying new therapeutic targets encoding proteins that regulate microtubule assembly and function specifically in cancer cells is critical. In the present study, we identified a candidate gene that promotes tumor progression, ribonucleic acid export 1 ( RAE1 ), a mitotic checkpoint regulator, on chromosome 20q through a bioinformatics approach using datasets of colorectal cancer (CRC), including The Cancer Genome Atlas (TCGA). RAE1 was ubiquitously amplified and overexpressed in tumor cells. High expression of RAE1 in tumor tissues was positively associated with distant metastasis and was an independent poor prognostic factor in CRC. In vitro and in vivo analysis showed that RAE1 promoted tumor growth, inhibited apoptosis, and promoted cell cycle progression, possibly with a decreased proportion of multipolar spindle cells in CRC. Furthermore, RAE1 induced chemoresistance through its anti–apoptotic effect. In addition, overexpression of RAE1 and significant effects on survival were observed in various types of cancer, including CRC. In conclusion, we identified RAE1 as a novel gene that facilitates tumor growth in part by inhibiting apoptosis and promoting cell cycle progression through stabilizing spindle bipolarity and facilitating tumor growth. We suggest that it is a potential therapeutic target to overcome therapeutic resistance of CRC. Abstract : In vitro and in vivo analysis showed that RAE1 promoted tumor growth and inhibited apoptosis of tumor cells, possibly with a decreased proportion of multipolar spindle cells in CRC. Furthermore, RAE1 induced chemoresistance through its anti–apoptotic effect. In conclusion, we identified RAE1 as a novel driver gene that inhibits apoptosis by stabilizing spindle bipolarity and facilitating tumor growth.